The transition from quantum field theory to one-particle quantum mechanics and a proposed interpretation of Aharonov–Bohm effect - Li, Benliang (2020)
In this article, we demonstrate a sense in which the one-particle quantum mechanics (OPQM) and the classical electromagnetic four-potential arise from the quantum field theory (QFT). In addition, the classical Maxwell equations are derived from the QFT scattering process, while both classical electromagnetic fields and potentials serve as mathematical tools to approximate the interactions among elementary particles described by QFT physics. Furthermore, a plausible interpretation of the Aharonov–Bohm (AB) effect is raised within the QFT framework. We provide a quantum treatment of the source of electromagnetic potentials and argue that the underlying mechanism in the AB effect can be understood via interactions among electrons described by QFT theory where the interactions are mediated by virtual photons.